2022
DOI: 10.1097/aln.0000000000004195
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Circuit from the Paraventricular Thalamus to the Bed Nucleus of the Stria Terminalis for the Regulation of States of Consciousness during Sevoflurane Anesthesia in Mice

Abstract: Background The neural circuitry underlying sevoflurane-induced modulation of consciousness is poorly understood. We hypothesized that the paraventricular thalamus-bed nucleus of the stria terminalis pathway plays an important role in regulating states of consciousness during sevoflurane anesthesia. Methods Rabies-virus-based transsynaptic tracing techniques were employed to reveal the neural pathway from the paraventricular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…While we chose to photoadduct in the rostral pons as proof of principle in studying systemic effects of local CNS anesthetic photolabel adduction, this same approach could be extended to multiple other brain regions previously shown to be involved in arousal and as targets for anesthetic effects. Numerous and disparately located CNS centers, including other areas of the pons, medulla, midbrain, hypothalamus, basal forebrain, thalamus, and cortex, have been demonstrated to be critical for anesthetic action or emergence from anesthesia ( Devor and Zalkind, 2001 ; Abulafia et al, 2009 ; Luo and Leung, 2009 ; Moore et al, 2012 ; Solt et al, 2014 ; Z. Zhang et al, 2015 ; Gelegen et al, 2018 ; Pal et al, 2018 ; Gao et al, 2019 ; Wang et al, 2019 ; J. Y. Li et al, 2022 ). Our results confirm that in vivo photoadduction produces local therapeutic-level concentrations of drug in ROIs.…”
Section: Discussionmentioning
confidence: 99%
“…While we chose to photoadduct in the rostral pons as proof of principle in studying systemic effects of local CNS anesthetic photolabel adduction, this same approach could be extended to multiple other brain regions previously shown to be involved in arousal and as targets for anesthetic effects. Numerous and disparately located CNS centers, including other areas of the pons, medulla, midbrain, hypothalamus, basal forebrain, thalamus, and cortex, have been demonstrated to be critical for anesthetic action or emergence from anesthesia ( Devor and Zalkind, 2001 ; Abulafia et al, 2009 ; Luo and Leung, 2009 ; Moore et al, 2012 ; Solt et al, 2014 ; Z. Zhang et al, 2015 ; Gelegen et al, 2018 ; Pal et al, 2018 ; Gao et al, 2019 ; Wang et al, 2019 ; J. Y. Li et al, 2022 ). Our results confirm that in vivo photoadduction produces local therapeutic-level concentrations of drug in ROIs.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitive SNPs associated with sedative and cardiovascular effects of sevoflurane are not identical, possibly due to the different mechanisms by which sevoflurane exerts these 2 effects. Sevoflurane acts on multiple parts of the central nervous system, including the reticular ascending activation system in the brain, the thalamus, and so on, to exert a sedative effect 27,28 . However, the main centers that control cardiovascular activity are the spinal cord and brain stem.…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane acts on multiple parts of the central nervous system, including the reticular ascending activation system in the brain, the thalamus, and so on, to exert a sedative effect. 27,28 However, the main centers that control cardiovascular activity are the spinal cord and brain stem.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is mounting proof that glial cells are involved and that sevoflurane acts on their GABA A receptors (Woll et al, 2018;Chung et al, 2022), thereby influencing their function. (2022) ↑indicated that the time is increasing, the EEG power increased or the c-Fos positive cells was increased. ↓indicated that the tme is decreasing or the EEG power decreased.…”
Section: Future Directionmentioning
confidence: 99%
“…After the inhibition of the PVT-BNST pathway, the time to LORR is reduced during sevoflurane anesthesia and the dose-response curve is shifted to the left. Optogenetic activation of the PVT-BNST showed the opposite trend (Li et al, 2022 ).…”
Section: Brain Areas and Circuitsmentioning
confidence: 99%